2019
DOI: 10.1088/1742-6596/1213/5/052051
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial intermetallic developments of Sn-3.0Ag-0.5Cu-2.0ZnO lead free solder

Abstract: The interfacial intermetallic compound growth behavior of Sn-3.0Ag-0.5Cu lead free solder joints with 2.0wt.% ZnO of micrometer was investigated in this study. Solder joints were fabricated in F4N reflow furnace at 255°Cfor less than 5min and thereafter aged at 150°C up to 240h. Results showed that the IMCs layer were almost layer type and grew thicker with extended aging time. The IMCs of Sn-3.0Ag-0.5Cu-2.0ZnO composite solder was diffusion controlled mechanism by diffusion growth kinetics analysis, moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The addition of ZnO particles has a similar effects. Qu et al showed that the ZnO micro-and nano-particles in SAC305 solder alloy decreased the IMC layer thickness at the solder-substrate interface [9]. They observed some wettability increase over 0.5 wt% as well [10].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of ZnO particles has a similar effects. Qu et al showed that the ZnO micro-and nano-particles in SAC305 solder alloy decreased the IMC layer thickness at the solder-substrate interface [9]. They observed some wettability increase over 0.5 wt% as well [10].…”
Section: Introductionmentioning
confidence: 99%
“…The ZnO has similar properties with other oxide ceramic nano-particle alloys in solder material. The ZnO micro or nano-particles added to SnAgCu based solder alloys have suppressed the IMC layer growth at the soldersubstrate interface [9][10]. It was shown in solder alloys that ZnO nano-particles decrease the diffusion coefficient, and this suppresses the formation and growth of the IMC layer.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ZnO addition has a similar effect to some extent. In the case of SnAgCu-based solder alloys, the addition of ZnO micro-and nanoparticles resulted in a thinner IMC layer at the solder-substrate interface [12][13]. The wettability was also increased slightly over 0.5 wt% addition [13].…”
Section: Introductionmentioning
confidence: 99%